Learning from lslam: Advocacy of Reproductive Rights in lndonesia Pesantren - Mas'udi, Masdar F.; Sciortino, Rosalia; Marcoes, Lies (Studia Islamika, 1997)
Articles written based on the experience of training in this field aims to build awareness of a method that can explain the relationship between religion and reproductive rights of women. Some of the key themes in this article seeks to reexamine the validity of Islamic texts concerning women's rights, the ideological assumptions behind the interpretation of the text, as well as how to build their awareness of the methods of the sexual rights of women.DOI: 10.15408/sdi.v4i2.781